Albanian National Museums: How to Overcome the Digital Gap Towards a Better National Heritage Promotion - Kamberi, Aurora (European Journal of Multidisciplinary Studies, 2021)
The digital and IT technologies are shaping the essential functions in our society where even the traditional culture heritage institutions such as museums are looking forward to figuring out the way to use a great range of possibilities for better promotion and visibility. The paper aims to set out the main issues that must be addressed if we consider to have a comprehensive understanding of the opportunities for a new perspective on Albania’s digitalized museums, as one of the most important cultural heritage institutions. Currently, the Albanian national museum network accounts for 14 museums of different typologies which are situated across the country, with a total of outdoors and in store collections of objects and artifacts. As of now, most Albanian museums have an online presence, with a variety of online information, however the paper seeks to interlink the promoting cultural heritage variables of museums using IT tools not merely to reproduce existing objects, but to actualize new ones through an interactive and educative environment. Since the digitalization of museums is a task that has combined efforts, budgets, and research by assessing the national culture policy of Albania, the paper also aims to explore the opportunities that may be taken in consideration by the policy - makers and museum managers in the country.
Keywords: Albania, national museums, oovercome, digital gap, national heritage promotion